Inclusion of phenolic bioactives in high amylose corn starch for gastro-intestinal delivery - Tarazi Riess, Hila; Shani Levi, Carmit; Lesmes, Uri (Frontiers in Nutrition, 2022)
Starch is a staple food component with intricate architectures, some of which can be utilized as polysaccharidic delivery vehicles for bioactive compounds. This work describes the use of high amylose corn starch (HACS) to fabricate V-amylose inclusion complexes entrapping capsaicin or curcumin. In line with past studies, X-ray diffraction, differential scanning calorimetry, static laser scattering and scanning electron microscopy help affirm the formation of V6III-type complexes. Such HACS complexes entrap capsaicin and curcumin in structures with higher levels of crystallinity compared to HACS alone (14.61±0.08%, 14.65±0.08% versus 10.24±0.24%, respectively), high levels of encapsulation efficiency (88.77±5.7% and 66.3±0.99%, respectively) but without significant differences in colloid sizes between the various inclusion complexes (58.25±1.34m or 58.98±2.32m, respectively). In turn, in-vitro gastro-intestinal digestion of HACS complexes with capsaicin or curcumin revealed both, phenolic bioactives significantly (p<0.05) attenuated the intestinal breakdown of HACS. Interestingly, this attenuated HACS digestibility was accompanied by high gastric retention of the payloads and their sustained release during 2 hr of exposure to intestinal conditions. Altogether, this work presents starch-based delivery systems that can entrap phenolic bioactives, release the payload in the intestine and possibly attenuate starch breakdown (because of its increased crystallinity). Thus, this work offers a platform for infusing foods with bioactive phenolics and stall the breakdown of starch.